Aplikasi Berbasis Web untuk Transaksi Penjualan Multi Vendor (Studi Kasus: UMKM BUMDes Lengkong, Bandung) - Mikael Octavianus Sihombing; Sukawati, Renny; Kastaman (eProceedings of Applied Science, 2024)
This Final Project discusses the implementation of sales applications for Micro, Small and Medium Enterprises (UMKM) in Lengkong village. This application is designed to assist UMKM in expanding the marketing reach of their products to a wider market share. In addition, this application can also calculate the income earned by UMKM, as well as monitor products by presenting general journal reports, ledgers, and product sales charts. The development and research method used in this project is the prototype development model. The programming language used is Hypertext Preprocessor (PHP), while My Structure Query Language (MySQL) is used as the database. With the implementation of this research and application, it is expected that MSMEs in Lengkong Village can increase efficiency in marketing their products and gain better insight into their sales performance. Keywords: UMKM, Sales, Multiple Vendors, Sales calculation, and PHP.